2014
DOI: 10.3832/ifor1045-007
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi as a tool to ameliorate the phytoremediation potential of poplar: biochemical and molecular aspects

Abstract: © iForest -Biogeosciences and Forestry IntroductionMany large areas around the world are contaminated with heavy metals (HMs) and/or organic compounds; most of these have not been remediated due to the high cost and technical drawbacks of currently available technologies. HMs tend to accumulate in soils and aquatic sediments and can enter the food chain leading to the biomagnification phenomenon thereby representing a risk to the environment and to human health (Clijsters et al. 1999). Some essential elements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 87 publications
0
18
1
Order By: Relevance
“…Levels of PTEs in soil may also affect the role of arbuscular mycorrhizal symbiosis (Audet and Charest, 2007), which can lead to an increase of plant metal uptake at low soil PTE concentrations as well as a reduction of PTE bioavailability via fungal metal-binding processes at high soil PTE levels. The mechanisms underlying metal accumulation may involve metallothioneins, small proteins that bind metals in plant detoxification process, as demonstrated in a greenhouse experiment (Cicatelli et al, 2014). Garg and Aggarwal (2011) also reported that AMF induced the production of chelating agents (phytochelatins) and antioxidants (glutathione) to reduce PTE toxicity and translocation in plant shoots.…”
Section: Effects Of Mycorrhizal Inoculationmentioning
confidence: 96%
See 3 more Smart Citations
“…Levels of PTEs in soil may also affect the role of arbuscular mycorrhizal symbiosis (Audet and Charest, 2007), which can lead to an increase of plant metal uptake at low soil PTE concentrations as well as a reduction of PTE bioavailability via fungal metal-binding processes at high soil PTE levels. The mechanisms underlying metal accumulation may involve metallothioneins, small proteins that bind metals in plant detoxification process, as demonstrated in a greenhouse experiment (Cicatelli et al, 2014). Garg and Aggarwal (2011) also reported that AMF induced the production of chelating agents (phytochelatins) and antioxidants (glutathione) to reduce PTE toxicity and translocation in plant shoots.…”
Section: Effects Of Mycorrhizal Inoculationmentioning
confidence: 96%
“…Mycorrhizal fungi can trigger root exudation of organic acids, and solubilize PTEs (Churchland and Grayston, 2014). Conversely, it is likely that the inoculation also decreased PTE mobility in other plots (P11, P23, F9 and F12), via metal-binding processes (Cicatelli et al, 2014). Moreover, the extractable PTE concentrations in soils was not correlated with the effect of inoculation on PTE accumulation by poplars (Fig.…”
Section: Effects Of Mycorrhizal Inoculationmentioning
confidence: 96%
See 2 more Smart Citations
“…There is recent evidence that the relationship with AMF can cause changes in DNA methylation of plants [15]. What is not known is whether AMF can in fact impact DNA methylation trangenerationally.…”
Section: Introductionmentioning
confidence: 99%